2015
DOI: 10.15252/embj.201490493
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated mi RNA biogenesis downstream of cellular stress and ALS ‐causing mutations: a new mechanism for ALS

Abstract: Interest in RNA dysfunction in amyotrophic lateral sclerosis (ALS) recently aroused upon discovering causative mutations in RNAbinding protein genes. Here, we show that extensive downregulation of miRNA levels is a common molecular denominator for multiple forms of human ALS. We further demonstrate that pathogenic ALS-causing mutations are sufficient to inhibit miRNA biogenesis at the Dicing step. Abnormalities of the stress response are involved in the pathogenesis of neurodegeneration, including ALS. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
188
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(212 citation statements)
references
References 107 publications
11
188
1
1
Order By: Relevance
“…Defects in miRNA biogenesis, for example via knockout of Dicer, has been correlated with decreased motor activity and survival, muscle atrophy, denervation, spinal cord sclerosis, and axonopathy in mice [113]. Additionally, previous studies have demonstrated decreased miRNA expression in the ventral lumbar spinal cord from patients with ALS [114], and also in spinal MN with ALS-causing mutations [115]. These results highlight the potential utility of miRNAs as biomarkers for ALS.…”
Section: Micrornamentioning
confidence: 74%
“…Defects in miRNA biogenesis, for example via knockout of Dicer, has been correlated with decreased motor activity and survival, muscle atrophy, denervation, spinal cord sclerosis, and axonopathy in mice [113]. Additionally, previous studies have demonstrated decreased miRNA expression in the ventral lumbar spinal cord from patients with ALS [114], and also in spinal MN with ALS-causing mutations [115]. These results highlight the potential utility of miRNAs as biomarkers for ALS.…”
Section: Micrornamentioning
confidence: 74%
“…Moreover, misfolded proteins, such as ALS-linked variants of superoxide dismutase 1 (SOD1), can specifically accumulate and aggregate with SGs, which influences their composition and dynamics and triggers an aberrant liquid-tosolid transition (Mateju et al, 2017). Importantly, pathogenic ALScausing mutations in FUS are sufficient to inhibit miRNA biogenesis (Eitan and Hornstein, 2016;Emde et al, 2015).…”
Section: Liquid-like Organelle Formation Through Phase Separationmentioning
confidence: 99%
“…Therefore, it is critical to understand how their expression is controlled -especially under stress conditions. miRNAs are prime candidates to control gene expression, as the miRNA expression profile is substantially changed in response to different stresses or diseases (Emde et al, 2015;Freiesleben et al, 2016;Lu et al, 2005;Marrone et al, 2012;Piwecka et al, 2015). This change in miRNA expression has a profound impact on the ability of the cell, or even the whole organism, to manage stress responses (Cicek et al, 2016;Edeleva and Shcherbata, 2013;Leung and Sharp, 2010;Mori et al, 2012).…”
Section: Liquid-like Organelle Formation Through Phase Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…knocking down DICER1 abolished behavioral resilience to stress. Chronic stress up-regulates cellular oxidative stress, which is known to inhibit microRNA biogenesis by modulating DICER1 activity [58] and altered intracellular reactive oxygen species production has been proposed to be a cause of idiopathic male infertility [59]. Future studies are required to clarify the mechanisms involved.…”
Section: Location and Mechanism For Stress-induced Modification Of Spmentioning
confidence: 99%